M-sequence-coded excitation for magneto-acoustic imaging. - Zhang, Shunqi; Ma, Ren; Yin, Tao; Liu, Zhipeng (Medical & Biological Engineering & Computing, 2019)
Magneto-acoustic imaging is a novel functional imaging method to electrical characteristics of tissue. It provides valuable tools for diagnosing early stage tumor and monitoring bioelectrical current. Common single short-pulse excitation limits SNR due to the short-pulse duration and low power of magneto-acoustic signal. In this study, we propose M-sequence-coded excitation and pulse compression approach to improve SNR of magneto-acoustic imaging. Simulations on the magneto-acoustic signal under different bit lengths M-sequence-coded excitation are performed. Experiments on the samples made of pork and graphite slices are done to validate the proposed coded excitation method. The SNR and sidelobe levels were investigated. The results showed when 7, 15, 31, 63, 127 bits M-sequence-coded excitations were applied onto the samples, SNR was improved by 17.4 dB, 24.2 dB, 30.6 dB, 37.6 dB, and 40.1 dB, respectively. For a similar SNR improvement, the total used time under coded excitation can be shortened to 9.4% under the single pulse excitation. The result indicates the M-sequence-coded excitation approach is effective to improve the magneto-acoustic signal SNR and shorten the imaging time. Graphical abstract SNR of the magneto-acoustic signal is significantly improved by the coded excitation than the pulse excitation, the reconstructed image of the front and back boundary of the pork can be seen clearly under the 7, 15, 31, 63, 127 bit M-sequence-coded excitations.